2012
DOI: 10.1158/1535-7163.mct-11-0921
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ATR-Dependent Signaling by Protoapigenone and Its Derivative Sensitizes Cancer Cells to Interstrand Cross-link–Generating Agents In Vitro and In Vivo

Abstract: DNA damage caused during cancer treatment can rapidly activate the ataxia telangiectasia-mutated (ATM) and ATM and Rad3-related (ATR)-dependent phosphorylation of Chk2 and Chk1 kinases, which are hallmarks of the DNA damage response (DDR). Pharmacologic inhibition of ATR causes a synthetic lethal effect on ATMor p53-defective cancers, suggesting that such inhibition is an effective way to improve the sensitivity of cancers to DNA-damaging agents. Here, both the natural compound protoapigenone (WYC02) and its s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 51 publications
(72 reference statements)
3
53
0
Order By: Relevance
“…To do this, we assessed whether elevated APOBEC3B might sensitise cells to a platinum salt, cisplatin used in combination with an ATR inhibitor (Wang et al , 2012) or a PARP inhibitor used in combination with either an ATR or WEE1 inhibitor. We found that cells with induced APOBEC3B expression exhibited an enhanced level of sensitivity to each of these combinations.…”
Section: Resultsmentioning
confidence: 99%
“…To do this, we assessed whether elevated APOBEC3B might sensitise cells to a platinum salt, cisplatin used in combination with an ATR inhibitor (Wang et al , 2012) or a PARP inhibitor used in combination with either an ATR or WEE1 inhibitor. We found that cells with induced APOBEC3B expression exhibited an enhanced level of sensitivity to each of these combinations.…”
Section: Resultsmentioning
confidence: 99%
“…In nude mice, 1 inhibited the growth of ovarian (MDAH-2774) and prostate (LNCap) cancer xenografts [33,34], while both compounds exerted such activity against cervical (HeLa) cancer xenografts [35,36]. Compound 2 was active against colorectal (HCT116) cancer xenografts in nude mice [28], and it was able to chemosensitize MDA-MB-231 breast cancer xenografts toward cisplatin possibly via the inhibition of DNA repair [10]. Moreover, 2 inhibited microvascularization in HeLa xenografts as well as in vivo angiogenesis both in zebrafish model and in nude mice [36].…”
Section: Discussionmentioning
confidence: 99%
“…As such, these compounds can severely interfere with the redox homeostasis of cancer cells on multiple levels, leading to an oxidative stress-mediated apoptosis [9]. Based on protoapigenone (PA; compound 1), a natural protoflavone derived from apigenin, a set of prospective leads is under development including the synthetic β-naphthoflavone derivative WYC0209 (compound 2) [10]. According to our previous results, these compounds are unlikely to be P-gp substrates; moreover, 6-methyl derivatives showed a mild selectivity against a murine cancer cell line transfected with this efflux transporter [11].…”
Section: Introductionmentioning
confidence: 99%
“…[12] The proapoptotic activityo fp rotoflavones is mediated by oxidative stress [13] and the inhibition of ATR-dependent signaling. [14] We have previously shown that 6-methylated protoflavoned erivatives exert mild selectivec ytotoxicity against am urine lymphoma cell line transfected with the human ABCB1 transporter, while other protoflavones, derived from apigenin, genkwanin or b-naphthoflavone, did not exhibit such selectivity. [15] Furthermore, protoapigenone and its 1'-O-butyl-and propargylether,t he b-naphthoflavone analogueW YC0209, 6-methylprotoflavone and 6-bromoprotoflavone showeds elective cytotoxicity againstc ertain MDR cancer cell lines, such as NCI-H460 human non-smallc ell lung carcinoma cells adapted to doxorubicin, U87 human glioma and DLD1 human colorectal cells, both adapted to paclitaxel.…”
Section: Introductionmentioning
confidence: 99%